2018
DOI: 10.1002/1873-3468.12953
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of peptide interactions that regulate PKCε activation

Abstract: Targeting the interaction between PKC isoforms and their anchoring proteins can specifically regulate kinase activity. εV1-2 and pseudoεRACK peptides, derived from the PKCε C2 domain, modulate its association with receptor for activated C-kinase 2 (RACK2) and thus its function. Details of these interactions remain obscure, and we therefore investigated binding of these peptides using biophysical techniques. Surface plasmon resonance (SPR) indicated that the inhibitory εV1-2 peptide bound to RACK2, and inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Signaling pathways and biological function are regulated by protein–protein interaction, often involving specific protein domains [ 53 , 54 , 55 ]. To examine whether α2 activates the TLR4 signal through its ability to bind TLR4, N2a cells were transfected (or not) with the α2 plasmid and protein extracts (24 h post-transfection) were studied for TLR4/α2 co-precipitation as previously described [ 38 , 39 ] and detailed in Section 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Signaling pathways and biological function are regulated by protein–protein interaction, often involving specific protein domains [ 53 , 54 , 55 ]. To examine whether α2 activates the TLR4 signal through its ability to bind TLR4, N2a cells were transfected (or not) with the α2 plasmid and protein extracts (24 h post-transfection) were studied for TLR4/α2 co-precipitation as previously described [ 38 , 39 ] and detailed in Section 2 .…”
Section: Resultsmentioning
confidence: 99%
“…An additional study using biophysical surface plasmon resonance (SPR) and nuclear magnetic resonance (NMR) indeed confirmed that εV1-2 bound to β -COP and inhibited PKCε binding. In the same study, they also found that ψεRACK did not bind to PKCε, suggesting that their mechanisms of action may be different [139]. The peptides above were developed based on sequence homology between isozymes, in a manner analogous to that depicted in Figure 4.…”
Section: Peptides Derived From Evolutionarily Conserved Sequencesmentioning
confidence: 99%